Medicalisation of childbirth in Cyprus - Hadjigeorgiou, Eleni (My University, 2009)
The main aim of this research was to explore the factors surrounding the extent to which midwives in Cyprus are advocating 'normal' childbirth.
Keywords: Midwives; Cyprus; Normal childbirth